Data Mining Techniques for Rainfall Data Using WEKA - Kumar, K. Anil; Reddy, S. Venkatramana; Sarojamma, B (International Journal of Computer Sciences and Engineering, 2022)
There are two types of monsoons or rainfall seasons in India: summer rainfall from October to March and winter rainfall from April to September. Rainfall plays a vital role in the cultivation, cropping, drinking and other purpose of human beings. Generally, in India, most of times the water source is from rain. In this paper, we are fitted isotonic regression model, linear regression, additive regression, Rep tree and simple linear regression by using machine learning models and are estimated using WEKA software for rainfall as dependent variable and time as an independent variable. The best model for the data is chosen using various accuracy measures like Absolute Mean Error, Root Mean Squared Error, Relative absolute error and Root Relative squared error.